Macam-Macam Sumber Pembiayaan Pendidikan di SMK Wijaya Putra Surabaya - Anugraheni Puspita (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
Vocational High School (SMK) is a school level that requires substantial funding, of course, in this case, educational institutions at the vocational level must prepare good funding sources. Funding for education is basically the key to achieving the goals and quality of educational institutions. This research was conducted to find out the sources of financing used in SMK Wijaya Putra Surabaya. This study used a qualitative method with observation, interviews and documentation with the principal of SMK Wijaya Putra Surabaya. The results of this study are that Wijaya Putra Surabaya Vocational School uses three sources of funds including funds from (1) the government, (2) funds from students, and (3) funds from students' parents. The management standards for Wijaya Putra Surabaya Vocational School are in accordance with the existing guidelines.